Addiction and Smoking Cessation - Hossain, Md Delwar; Islam, SAHM Mesbahul; Rashid, Md Mamunur; Chowdhury, Md Ashfaqul Islam; Bennoor, Kazi Saifuddin; Patwary, Md Ismail (Medicine Today, 2015)
Cigarette smoke contains a deadly mix of more than 7,000 chemicals, hundreds are toxic and about 70 can cause cancer. Cigarette smoke can cause serious health problems, numerous diseases and death. Fortunately, people who stop smoking greatly reduce their risk for disease and premature death. Although the health benefits are greater for people who stop at earlier ages, cessation is beneficial at all ages. There are various methods and approaches in quitting smoking. Currently, there are about 1.3 billion smokers the world, most (84%) of them in developing countries.If current smoking trends continue, tobacco will kill 10 million people each year by 2020. Medicine Today 2015 Vol.27(1): 30-33